Validating left atrial fractionation and low-voltage substrate during atrial fibrillation and sinus rhythm—A high-density mapping study in persistent atrial fibrillation - Huang, Taiyuan; Chen, Juan; Müller-Edenborn, Björn; Mayer, Louisa; Eichenlaub, Martin; Moreno Weidmann, Zoraida; Allgeier, Juergen; Bohnen, Marius; Lehrmann, Heiko; Trenk, Dietmar; Schoechlin, Simon; Westermann, Dirk; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Low-voltage-substrate (LVS)-guided ablation for persistent atrial fibrillation (AF) has been described either in sinus rhythm (SR) or AF. Prolonged fractionated potentials (PFPs) may represent arrhythmogenic slow conduction substrate and potentially co-localize with LVS. We assess the spatial correlation of PFP identified in AF (PFP-AF) to those mapped in SR (PFP-SR). We further report the relationship between LVS and PFPs when mapped in AF or SR. Materials and methods Thirty-eight patients with ablation naïve persistent AF underwent left atrial (LA) high—density mapping in AF and SR prior to catheter ablation. Areas presenting PFP-AF and PFP-SR were annotated during mapping on the LA geometry. Low-voltage areas (LVA) were quantified using a bipolar threshold of 0.5 mV during both AF and SR mapping. Concordance of fractionated potentials (CFP) (defined as the presence of PFPs in both rhythms within a radius of 6 mm) was quantified. Spatial distribution and correlation of PFP and CFP with LVA were assessed. The predictors for CFP were determined. Results PFPs displayed low voltages both during AF (median 0.30 mV (Q1–Q3: 0.20–0.50 mV) and SR (median 0.35 mV (Q1–Q3: 0.20–0.56 mV). The duration of PFP-SR was measured at 61 ms (Q1–Q3: 51–76 ms). During SR, most PFP-SRs (89.4 and 97.2%) were located within LVA (<0.5 mV and <1.0 mV, respectively). Areas presenting PFP occurred more frequently in AF than in SR (median: 9.5 vs. 8.0, p = 0.005). Both PFP-AF and PFP-SR were predominantly located at anterior LA (>40%), followed by posterior LA (>20%) and septal LA (>15%). The extent of LVA < 0.5 mV was more extensive in AF (median: 25.2% of LA surface, Q1–Q3:16.6–50.5%) than in SR (median: 12.3%, Q1–Q3: 4.7–29.4%, p = 0.001). CFP in both rhythms occurred in 80% of PFP-SR and 59% of PFP-AF (p = 0.008). Notably, CFP was positively correlated to the extent of LVA in SR (p = 0.004), but not with LVA in AF (p = 0.226). Additionally, the extent of LVA < 0.5 mV in SR was the only significant predictor for CFP, with an optimal threshold of 16% predicting high (>80%) fractionation concordance in AF and SR. Conclusion Substrate mapping in SR vs. AF reveals smaller areas of low voltage and fewer sites with PFP. PFP-SR are located within low-voltage areas in SR. There is a high degree of spatial agreement (80%) between PFP-AF and PFP-SR in patients with moderate LVA in SR (>16% of LA surface). These findings should be considered when substrate-based ablation strategies are applied in patients with the left atrial low-voltage substrate with recurrent persistent AF.